Highlighting attenuated total reflection Fourier transform infrared spectroscopy for rapid serum analysis - Dorling, Konrad M.; Baker, Matthew J. (Trends in biotechnology (Regular ed.), 2013)
Recent studies have been more clinically relevant, and have shown ATR-FTIR coupled with multivariate analysis techniques to be effective and comparable in standards to current clinical detection and diagnosis methods, in the accurate detection of renal failure [10], ovarian and endometrial cancers [11], and basal cell carcinoma [12] through the analysis of human blood serum. [...]there is a clear place for the use of ATR-FTIR instruments in the clinical setting, especially in the form of a serum screening and diagnostic tool for a plethora of diseases with further analysis of larger samples sets, ATR-FTIR has the potential to provide a rapid, dynamic, and responsive diagnostic environment based upon objective measures.